Bunting Lolo: The Dialectics of State, Islamic Law, and Culture in Marriage Practice among Island Communities in South Sulawesi - Abd. Kadir Ahmad; Sabara; Arafah, Sitti; Muhamamd Nur; Nur Fadhilah Mappaselleng (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
This study intends to explore the socio-cultural construction of island communities in South Sulawesi that fosters the tradition of bunting lolo (child marriage), including the influencing factors and its dialectic with the state and Islamic law. A critical ethnographic method was adopted with the island communities as the research subject, while the culture and practice of bunting lolo constitute the units of analysis. Data were collected from the communities of Kodingareng (Makassar City) and Badi (Pangkajene Islands Regency) island, both part of the Spermonde Islands. The result showed that the practice of bunting lolo has become a tradition based on social, cultural, economic, and religious constructs. In the contemporary context, bunting lolo is a solution to 'balerek' or promiscuity among adolescents, both boys and girls. This practice conflicts with the minimum marriage age regulation of 19 years stated in Marriage Law No. 16 of 2019. Consequently, bunting lolo manifests the dialectic between state, Islamic law, and local culture in marriage practices within the island communities in which state regulation is found to be less considered than the other two.